Emprendimiento social como modelo de gerencia pública en entidades gubernamentales (2020)
The purpose of the research was to analyze social entrepreneurship as a model of public management in government entities, taking as a theoretical reference the approaches of the authors: Merino (2013), Osterwalder and Pigneur (2010), Mohamed (2017), Raina (2018), Santos (2017), Ahlgren (2017), among others. The study is framed within the positivist paradigm quantitative approach of analytical type, with field design, not experimental, transversal. The population was conformed by the executives of the governmental entities of the District order of the City of Santa Marta belonging to the executive branch, specifically secretaries of office and area coordinators, making for it a population census. A frequency scale questionnaire was used to collect the perception of the respondents regarding the variables, which was validated by the trial of 8 experts and their reliability measured through a pilot test equivalent to 97%. The results were analyzed by inferential statistics, with the ANOVA and Post Hot test of Tukey. After studying the data in depth, it was evident that the variable business model dimension of social entrepreneurship, presents discrepancies between the groups’ means, placing the communication strategy and the recipients in the high range, but at a moderate level, the value proposition as the approach to the client aspects that are recommended to strengthen to make feasible its implementation.